2020
DOI: 10.1186/s12887-020-02340-1
|View full text |Cite
|
Sign up to set email alerts
|

Does zinc with and without iron co-supplementation have effect on motor and mental development of children? A systematic review and meta-analysis

Abstract: Background Effects of zinc with and without iron co-supplementation on child development are uncertain therefore the aims of this systematic review were to explore whether supplementation with zinc alone and zinc with iron in children aged 0–5 years old have beneficial or adverse effects on their mental and motor development. Method We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, CINAHL, Web of Science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Compared with no zinc intakes, the effect from lower supplementary zinc intakes could consistently be applied to other physical development parameters, including head circumference change ( 15 ), height-for-age z-scores (HAZ) change ( 15 ), MUAC ( 16 ), MUAC change ( 15 ), WAZ change ( 15 ), HAZ ( 15 , 16 ), weight for height z-scores ( 16 ) and psycho-motor development ( 39 ) as well as adulthood body fat percentage ( 40 ), body mass index (BMI) change ( 40 ), hip circumference ( 40 ), waist circumference change ( 40 ) and waist-to-hip ratio ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with no zinc intakes, the effect from lower supplementary zinc intakes could consistently be applied to other physical development parameters, including head circumference change ( 15 ), height-for-age z-scores (HAZ) change ( 15 ), MUAC ( 16 ), MUAC change ( 15 ), WAZ change ( 15 ), HAZ ( 15 , 16 ), weight for height z-scores ( 16 ) and psycho-motor development ( 39 ) as well as adulthood body fat percentage ( 40 ), body mass index (BMI) change ( 40 ), hip circumference ( 40 ), waist circumference change ( 40 ) and waist-to-hip ratio ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from derivative diseases, we can also firmly believe that mental and motor development are strengthened by zinc supplementations. Yet from Tam's, Warthon-Medina's and Sajedi's studies, no statistically significant correlations were found between supplementary zinc intake (<20 mg/d) and mental development (MD: −0.15 point, 95% CI: −2.38, 2.09) ( 16 ), intelligence (SMD: 0.00 point, 95% CI: −0.12, 0.13) ( 7 ) and psycho-motor development (SMD: 0.30 point, 95% CI: −0.24, 0.83) ( 39 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, no control group was included in that study. In agreement with a lack of zinc deficiency in ASDs, a meta-analysis including 25 studies and over 11,000 participants found a lack of efficacy of zinc supplementation on child mental and motor development up to nine years of age [ 372 ].…”
Section: Therapeutic Potential Of Zinc In Humansmentioning
confidence: 85%
“…Furthermore, no study offered information regarding cognitive scores, Intelligence Quotients (IQs), or any potential side effects of zinc supplementation. Thus, there is no substantial proof to suggest that providing zinc supplements to infants or children leads to enhanced motor skills or cognitive development [59].…”
Section: Discussionmentioning
confidence: 99%